HCLs digital open innovation : enhancing business model effectiveness through talent and customer acquisition, development, and retention - Darwin, Solomon N., (SAGE Knowledge. Cases., 2017)
This case study provides an illustration of how the intersection of new digital technologies mobile devices, cloud computing, and online collaboration is now transforming the way organizations will conduct business in the future. In late 2014, faced with the challenges of the inherent inefficiencies of operating within a $6.8 billion corporationwith over 110,000 employees located across 31 countriesand contending within the hyper-competitive $1 trillion global IT services industry, divisional executives at India-based HCL Technologies took the initiative to launch Starting Point, an internal centralized digital platform, for two of its key verticalsLife Sciences/Health Care and Public Servicesthat made up 20 percent of the companys revenue. Realizing that many of its current employees were already leading digital lives and were now almost always connected to their personal handheld devices, this new centralized digital platform had two key goals by making company data more readily-available on mobile phones and tablets: 1) to enhance the new hire on-boarding process and 2) to empower employees so that they could have more-effective customer discussions that would ultimately lead to more business-to-business sales. By making this transition from analog to digital, HCL Technologies executives believed that Starting Point would improve organizational agility, hasten internal decision making and increase employee efficiencies. This case tells the Starting Point story in three parts: Recognition of the need for a centralized digital platform and mobile strategy; execution of the initial digital platform over a six-week period; and an evaluation of the digital platforms benefits. The case also describes how the Starting Point project benefitted from HCLs entrepreneurial culture, which has been part of the companys DNA since its founding in 1976.